Responsabilidade Social da Ciência da Informação: o conceito da temática a partir dos registros dos Programas de Pós-Graduação em Ciência da Informação no Brasil - Dantas, Esdras Renan Farias (2016)
Its horizon analyze the concepts of social responsibility identified from dissertations and theses of Graduate Programs in Information Science (GPIS) in Brazil, noted that there are the thematic approaches with other issues versed in other areas of knowledge. If so, it intends to consider how relationships affect a concept of social responsibility to the field of Information Science. To develop research, we leave the wide SR concept, sharing the analysis of Ashley (2003), the concept of Information Science presented by Taylor (1966) and social responsibility concepts of Information Science of Du Mont (1991) and Wersig and Neveling (1975), as well as the evolution of these concepts advocated by Dantas and Garcia (2013). The field of research it is of Brazilian GPIS. In order to achieve the methodological standardization advocated by scientific rigor, defined as a research field programs that use DSpace as the management system of the respective repositories to allow retrieve documents by area of knowledge, union needs of the terms and the content of the documents. With it is understood, the concept of SR to the field of IC has relationship with 18 themes: accessibility; ethical issues; citizenship; Communication; Education; Social Science Information Service; Function Professional Information; social function of information units; digital inclusion and exclusion; social inclusion and exclusion; public policy information; preservation of memory; Archival social responsibility; social responsibility and science; corporate social responsibility; university social responsibility; environmental responsibility, and; Sociology. Per se, such issues do not explain all aspects of the flow of information and the means to process it for optimal access and use, as prescribed initial concept of IC, made in the Georgia Tech Conference. This is easy to understand given that the RS is presented as sociafunctions leading institutions and professionals to promote – extrapolating purelyl operational activities – accessibility, digital and social inclusion, social responsibility with science, with business, with the institutions of higher education, environmental, etc. Or influence the origin, dissemination, storage, organization, retrieval, interpretation and use of information. What it would be like to refer to the ways and means to formalize the flow of information. With regard to the categories represented fields of knowledge, listed Educational, Social Communication, Librarianship, the Archival, museology, sociology and management to the field of IC in its most intimate relationship with SR. The latter, although not as exposed category, visibly permeates discussions on the topic CSR, and implicitly understand their contributions. Finally, given the increasing number of studies that follow on the RS applied to CI, lined the acceptance of the concept in the area, we believe it is appropriate to represent the Science of Social Responsibility of the information by the acronym ICSR. With this, we offer ICSR as the concept of representation to that grants the familiar theme among researchers and professionals, supporting the implementation of the understanding and its importance to the area of IC.